Water law in India an introduction to legal instruments - Cullet, Philippe; Koonan, Sujith (New Delhi : Oxford University Press, 2011)
This work pieces together key legislative instruments and policy documents to provide an overarching picture of the legal regime and regulations related to water in India. It also brings out the complexity in the structure of laws due to variations at the levels of their implementation, i.e., at the international, national, state, municipal, and panchayat levels.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: Water -- Law and legislation -- India; Water-supply -- Government policy -- India; Law